2018
DOI: 10.1177/2472630317751840
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Review on Asiatic Acid and Its Derivatives: A Potential Compound

Abstract: Natural triterpenes represent a group of pharmacologically active and structurally diverse organic compounds. The focus on these phytochemicals has been enormous in the past few years, worldwide. Asiatic acid (AA), a naturally occurring pentacyclic triterpenoid, is found mainly in the traditional medicinal herb Centella asiatica. Triterpenoid saponins, which are the primary constituents of C. asiatica, are commonly believed to be responsible for their extensive therapeutic actions. Published research work has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 144 publications
0
60
0
Order By: Relevance
“…The molecular mechanisms underlying the various biological activities of AA have been described for malarial diseases as it is driven by OS. The pharmacological properties of AA and its derivatives inhibit multiple pathways of intracellular signaling molecules and transcription factors that are involved in the various stages of acute and chronic diseases [78]. The anti-inflammatory [79], antihyperlipidemia, malarial hypoglycaemia ameliorative effective [30], neuroprotective, reno-protective effects [80] and other activities of AA have an intricate and elaborate pattern, amongst the triterpenes, that is envisaged on the pleiotropic characteristics bed rocked on its anti-oxidative pro-oxidative properties and redox reactivity [81,82].…”
Section: Asiatic Acid (Aa) Administration and Oxidative Stress-drivenmentioning
confidence: 99%
“…The molecular mechanisms underlying the various biological activities of AA have been described for malarial diseases as it is driven by OS. The pharmacological properties of AA and its derivatives inhibit multiple pathways of intracellular signaling molecules and transcription factors that are involved in the various stages of acute and chronic diseases [78]. The anti-inflammatory [79], antihyperlipidemia, malarial hypoglycaemia ameliorative effective [30], neuroprotective, reno-protective effects [80] and other activities of AA have an intricate and elaborate pattern, amongst the triterpenes, that is envisaged on the pleiotropic characteristics bed rocked on its anti-oxidative pro-oxidative properties and redox reactivity [81,82].…”
Section: Asiatic Acid (Aa) Administration and Oxidative Stress-drivenmentioning
confidence: 99%
“…Asiatic acid (AA; C 30 H 48 O 5 ; Fig. 1A), which is chemically known as 2,3,23-trihydroxyurs-12-ene-28-oic-acid, is a pentacyclic triterpenoid compound extracted from the traditional Chinese medicinal herb Centella Asiatica (17). Previously, numerous studies have demonstrated that AA possesses various pharmacological properties, including hepatoprotective, neuroprotective, antioxidant, anti-inflammatory, anti-hyperglycemic and anticancer properties (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Asiatic acid (AA), a pentacyclic triterpene isolated from Centella asiatica [13], has been reported to exhibit a variety of pharmacological effects, including antioxidant, anti-inflammatory, and hepatoprotective activities [14][15][16]. Particularly, recent studies demonstrate that AA inhibits cardiac hypertrophy [17] and liver fibrosis [18].…”
Section: Introductionmentioning
confidence: 99%